Reforma de la ley del aborto, Ley Orgánica 1/2023; Implicaciones para la práctica profesional - Ainoa Biurrun-Garrido; Victoria García-Garro; Carme Perelló-Iñiguez; Gerard Colomar-Pueyo (Universitat de Barcelona, 2023)
Objective. To determine the professional implications of the application of Organic Law 1/2023. Methodology. This work analyses, from an ethical-legal perspective, the reform of the abortion decriminalization law. Results and discussion. Organic Law 1/2023 reforms the abortion law in Spain. The main differences in relation to the previous law are: 1. Consent: Women over the age of 16 can make the decision to abort without the consent of their legal representatives. 2. State registry of conscientious objection for health professionals. 3. Information: Health professionals must provide complete and truthful information about abortion options, risks, and consequences. The new law eliminates the three-day reflection period between the initial consultation and the procedure. Conclusions. The new abortion law in Spain aims to expand access to abortion services and improve reproductive rights. From a professional perspective, its changes have implications for the health care providers who attend women. It is important that these professionals are informed and updated about the new law and the obligations it entails. Health services must be prepared to offer information and support to women and to guarantee the deadlines and requirements established in the law.